(untitled) (Kindle, 2022)
An association of melatonin levels with age disease initiation of autoimmune diseases and pineal calcification was reported while an inverse association between melatonin levels and disease duration was shown, respectively. Recent investigations showed that melatonin’s serum and plasma levels as well as the 6-sulphatoxymelatonin (aMT6-s) the major melatonin metabolite urine levels were significantly lower in patients with autoimmune diseases compared with healthy controls. The accumulating evidence that disrupted melatonin production may contribute to the pathogenesis of autoimmune diseases led the researchers to assess gene variations which are essential for melatonin biosynthesis and analyze whether these variants constitute a risk for development of autoimmune diseases. In this regard , investigations conducted on cases with autoimmune diseases showed that the single gene polymorphism (SNPs) of tryptophan hydroxylase 2 (TPH2) gene was correlated with high risk of severe disability in patients. Therefore, in this book we aimed to review role of melatonin in pathogenesis and treatment of autoimmune diseases.